The Influence of Movement Imitation Therapy on Neurological Outcomes in Children Who Have Experienced Adverse Perinatal Conditions - Zhanna Zhussupova; Dinmukhamed Ayaganov; Gulmira Zharmakhanova; Gulzhanat Nurlanova; Latina Tekebayeva; Ayten Mamedbayli (West Kazakhstan Medical Journal)
This study aimed to evaluate the effectiveness of early intervention (EI) for infants at high risk for cerebral palsy (CP), particularly in the context of their neurological development. The study was conducted at the Regional Perinatal Center in Aktobe, Kazakhstan, and included 69 preterm infants with adverse neonatal periods. The infants were divided into two groups: the first group (n=50) began EI at 42 weeks postmenstrual age, while the second group (n=19) started at 52 weeks. Both groups underwent general movements assessment (GMA) and motor activity monitoring using general movement optimality score (GMOS). Results showed that infants receiving EI earlier demonstrated significant improvements in movement quality and a reduced risk of adverse neurological outcomes compared to the control group. The findings highlight the importance of early detection and intervention, as well as the need for implementing early diagnostic programs for infants at risk.